Air Stable Iron(II) PNP Pincer Complexes as Efficient Catalysts for the Selective Alkylation of Amines with Alcohols. Issue 23 (23rd November 2016) - Mastalir, Matthias; Stöger, Berthold; Pittenauer, Ernst; Puchberger, Michael; Allmaier, Günter; Kirchner, Karl
Abstract: A series of well‐defined iron(II) complexes of the types [Fe(PNP)Br2 ] and [Fe(PNP)(CO)Br2 ] with PNP pincer ligands based on triazine and pyridine backbones were prepared and fully characterized. These complexes were tested as catalysts for the alkylation of amines by alcohols. The high‐spin complexes [Fe(PNP)Br2 ] are catalytically inactive. The low‐spin complexes [Fe(PNP)(CO)Br2 ] bearing a carbonyl co‐ligand efficiently and selectively convert primary alcohols and aromatic and benzylic amines selectively into mono‐ N ‐alkylated amines in good to excellent isolated yields. A mechanistic proposal is given. Abstract :